The Influence of Government Expenditures in the Infrastructure Sector, Number of Tourists, Number of Hotels, and Number of Restaurants on the Tourism GRDP Forming Sector 2015-2019 - Atmana Putri, Rahayu; Yuliawan, Dedy (Lafadz Jaya Publisher, 2024)
This study aims to determine the effect of government spending on the infrastructure sector, the number of tourists, the number of hotels, and the number of restaurants on the Gross Regional Domestic Product Forming Sector of Tourism in the provinces of East Java, West Java, Central Java, DKI Jakarta, and Bali in 2015-2019. This study uses secondary data obtained from the Central Bureau of Statistics and the Directorate General of Balance. The analysis technique used in this research is panel data regression using the Eviews 10 computer application program. The results of this study indicate that the variables of government spending in the infrastructure sector, the number of tourists, and the number of restaurants have a positive and significant effect on the Tourism Gross Regional Domestic Product Forming Sector while the number of hotels has a negative and significant effect on the Tourism Gross Regional Domestic Product Forming Sector.